Seeds of Success : Stories of IFC’s Work to Improve the Lives of Women in Agribusiness Value Chains - International Finance Corporation (Washington, DC, 2022)
According to the e Food and Agriculture Organization (FAO), women make up on average forty-three percent of the agricultural workforce in developing countries. Female participation in value chains is critical, yet they still face gender-specific constraints and challenges in owning, accessing, and controlling resources that affect their productivity, livelihood, and income. These are stories of collaboration, gender advancement, and women empowerment. IFC believes in creating and implementing Gender-Smart Solutions to close gender gaps in the sector, thus increasing agricultural yields and revenues, improving wages, and helping women expand to new, favorable markets.